2006
DOI: 10.1097/01.mnm.0000230078.25609.2b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new expert system for fully automated detection of the Alzheimer's dementia pattern in FDG PET

Abstract: The results of the present study suggest that the PALZ tool provides similar performance for the detection of the typical Alzheimer's disease pattern in FDG PET images as an experienced reader supported by SPM. The PALZ tool is fully automated, easy to use, and insensitive to the spatial resolution of the PET scanner used. Therefore, it has the potential for widespread clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The region of interest from which the PET score is being derived had been identified in the original cross-sectional sample by the correlation of those voxels with MMSE (11), thus making its construction well suited for monitoring of disease progression. The robustness of the procedure has also been demonstrated previously in additional cross-sectional samples (12,16). We are therefore confident that the estimate of the variance associated with the PET score measurements described in the present paper is representative for the general application of the technique.…”
Section: Discussionsupporting
confidence: 55%
“…The region of interest from which the PET score is being derived had been identified in the original cross-sectional sample by the correlation of those voxels with MMSE (11), thus making its construction well suited for monitoring of disease progression. The robustness of the procedure has also been demonstrated previously in additional cross-sectional samples (12,16). We are therefore confident that the estimate of the variance associated with the PET score measurements described in the present paper is representative for the general application of the technique.…”
Section: Discussionsupporting
confidence: 55%
“…In a study of 22 patients and 18 normal controls, the PALZ tool was found to have 100% sensitivity and 83 % specificity, for the diagnosis of AD. This relatively decreased specificity was attributed to an attenuation correction artifact encountered in this study because of the use post-injection transmission scans [105].…”
Section: Fdg Pet/mr and The Use Of Standardized Analysesmentioning
confidence: 81%
“…In addition, patients diagnosed with mild cognitive impairment (MCI), which is considered to be a prodromal stage of AD (Albert et al, 2011; Petersen, 2000; Petersen et al, 1999), also show consistent brain metabolic reductions relative to healthy older adults (HC), particularly in regions of the parietal and temporal lobes (Del Sole et al, 2008; Li et al, 2008; Lowe et al, 2009; Mosconi et al, 2005). In addition to evaluating brain metabolism in MCI and AD for the purpose of understanding the impact of disease on resting-brain metabolism, FDG PET measures have also been assessed for sensitivity in early diagnosis, alone or in conjunction with other imaging modalities (e.g., magnetic resonance imaging (MRI)) and cerebrospinal fluid (CSF) protein levels (Chetelat, Desgranges, de la Sayette, Viader, Eustache, et al, 2003; de Leon et al, 2007; Drzezga et al, 2005; Habeck et al, 2008; Herholz et al, 2002; Kim et al, 2010; Lucignani & Nobili, 2010; Minoshima, Frey, Koeppe, Foster, & Kuhl, 1995; Mosconi, 2005; Mosconi et al, 2010; Mosconi et al, 2004; Mosconi et al, 2007; Nobili et al, 2008; Pontecorvo & Mintun, 2011; Rimajova et al, 2008; Silverman et al, 2001; von Borczyskowski et al, 2006). In addition, FDG PET scans have shown utility as part of a clinical diagnostic evaluation protocol and potentially in therapeutic intervention trials (Alexander, Chen, Pietrini, Rapoport, & Reiman, 2002; Bohnen, Djang, Herholz, Anzai, & Minoshima, 2012; Chow et al, 2011; Herholz, 1995; W.…”
Section: Introductionmentioning
confidence: 99%